Medium-to-high prevalence of screening-detected parkinsonism in the urban area of Tehran, Iran: data from a community-based door-to-door study - Fereshtehnejad SM (Dove Medical Press, 2015)
Seyed-Mohammad Fereshtehnejad,1,2 Mahdiyeh Shafieesabet,3 Arash Rahmani,4 Ahmad Delbari,1,5 Johan Lökk1,6 1Division of Clinical Geriatrics, Department of Neurobiology, Care Sciences, and Society (NVS), Karolinska Institutet, Stockholm, Sweden; 2Firoozgar Clinical Research Development Center (FCRDC), Firoozgar Hospital, 3Medical Student Research Committee (MSRC), Faculty of Medicine, 4Mental Health Research Center, Tehran Institute of Psychiatry, School of Behavioral Sciences and Mental Health, Iran University of Medical Sciences, Tehran, Iran; 5Iranian Research Center on Aging, University of Social Welfare and Rehabilitation, Tehran, Iran; 6Department of Geriatric Medicine, Karolinska University Hospital, Stockholm, Sweden Introduction: Parkinsonism occurs in all ethnic groups worldwide; however, there are wide variations in the prevalence rates reported from different countries, even for neighboring regions. The huge socioeconomic burden of parkinsonism necessitates the need for prevalence studies in each country. So far, there is neither data registry nor prevalence information on parkinsonism in the Iranian population. The aim of our study was to estimate the prevalence rate of probable parkinsonism in a huge urban area in Iran, Tehran using a community-based door-to-door survey.Materials and methods: We used a random multistage sampling of the households within the network of health centers consisting of 374 subunits in all 22 districts throughout the entire urban area of Tehran. Overall, 20,621 individuals answered the baseline checklist and screening questionnaire and data from 19,500 persons aged ≥30 years were entered in the final analysis. Health care professionals used a new six-item screening questionnaire for parkinsonism, which has been previously shown to have a high validity and diagnostic value in the same population.Results: A total of 157 cases were screened for parkinsonism using the validated six-item questionnaire. After age and sex adjustment based on the Tehran population, the prevalence of parkinsonism was calculated as 222.9 per 100,000. Using the World Health Organization’s World Standard Population, the standardized prevalence rate of parkinsonism was 285 per 100,000 (95% confidence interval 240–329). The male:female ratio of probable parkinsonism was calculated as 1.62, and there was a significant increase in the screening rate by advancing age.Conclusion: The calculated rates for the prevalence of parkinsonism in our study are closer to reports from some European and Middle Eastern countries, higher than reports from Eastern Asian and African populations, and lower than Australia. The prevalence rate of >200 in 100,000 for parkinsonism in Tehran, Iran could be considered a medium-to-high rate. Keywords: parkinsonism, Parkinson’s disease, prevalence, door-to-door survey, population-based